2022
DOI: 10.1038/s12276-022-00828-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a spontaneous pain indicator based on brain cellular calcium using deep learning

Abstract: Chronic pain remains an intractable condition in millions of patients worldwide. Spontaneous ongoing pain is a major clinical problem of chronic pain and is extremely challenging to diagnose and treat compared to stimulus-evoked pain. Although extensive efforts have been made in preclinical studies, there still exists a mismatch in pain type between the animal model and humans (i.e., evoked vs. spontaneous), which obstructs the translation of knowledge from preclinical animal models into objective diagnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In previous research, our team developed an algorithm that uses DL to detect pain from S1 calcium signals (Yoon et al, 2022 ). In the current study, we introduced an ML model that, while aiming to achieve similar goals as our prior research, offers a range of distinct benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous research, our team developed an algorithm that uses DL to detect pain from S1 calcium signals (Yoon et al, 2022 ). In the current study, we introduced an ML model that, while aiming to achieve similar goals as our prior research, offers a range of distinct benefits.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the complete Freund's adjuvant (CFA) model (Yoon et al, 2022 ), 10 μl of CFA were injected subcutaneously into the plantar surface of the right hind paw. To establish the chemotherapy-induced peripheral neuropathy model (Kim W. et al, 2016 ), oxaliplatin (6 mg/kg) was treated intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that S1 can antagonistically modulate itch and pain [ 20 , 21 ]. In our previous study, we showed that itch and pain could be distinguished by a deep-learning algorithm based on S1 neuronal activity, implying that S1 neurons have a distinct response pattern for itch and pain [ 22 ]. However, how S1 neurons differentially encode these two distinct sensations and whether S1 represents the interaction between two sensations remains unexplored at the cellular level.…”
Section: Introductionmentioning
confidence: 99%